The Geography of Dayak Dialect in Landak Regency, West Kalimantan - Patriantoro Patriantoro (Indonesian Journal of EFL and Linguistics, 2021)
The aims of this research entitled “The Geography of Dayak Dialect in Landak Regency, West Kalimantan” were to describe lexical variation, calculate the difference in lexical variation between observation points, map lexical variation, and create isogloss documents lexically. The form of this research was descriptive qualitative; the source of data for the Dayak language used in Landak was the native speakers of Dayak language. The methods used for data analysis were synchronous comparative method and triangular comparative technique between villages; while the formula used to analyze the data was the Dialectometric. The results from the data analysis, difference in lexical variation calculation between observation of Dayak language in Landak regency indicated that there found language differences, dialect differences, sub-dialect differences speech differences and no differences. Different lexical variations existed in the study area. There found 2 languages from the mapping of lexical variations of the Dayak language in Landak Regency. The first language included 4 observation points (Air Besar/Serimbu) called as S language (Serimbu) and the second language at observation points ((1, 2, 3, 5, 6, 7 / Sompak, Darit, Landak, Pahoman, Sengah Temila, and Mandor ) is referred to as the K language (Kanayatn). The K (Kanayatn) languge itself has 2 dialects, namely first dialect at the Observation point (3) Landak (members of Landak), the second dialect at the point of observation (1,2,5,6,7) Darit dialect (members of Sompak, Darit, Pahoman, Sengah Temila, and darit). The lexical isogloss documents separated the different language area with the percentage of 80.1%-100%; dialect areas 50.1%-80%; sub-dialect area 30.1%-50%; regional different in speech 20.1%-50%; and no difference with the range of 0-20%.